Improving teacher quality a guide for education leaders - Laine, Sabrina W. M.; Behrstock-Sherratt, Ellen; Lasagna, Molly; ebrary, Inc. (San Francisco : Jossey-Bass, 2011)
"Techniques for the difficult task of improving teacher quality No one stakeholder group can realize lasting change on their own; nor can any reform initiative focusing on just one type of strategy create the workplace conditions needed to truly build capacity within the education profession. Rather, stakeholders must focus on collaborating, reaching common understanding, and prioritizing for ultimate impact on the quality of teachers and teaching. This book discusses research and concrete examples of practice tied to teacher quality intended to improve eight key interrelated factors: Preparation; Recruitment; Hiring; Induction; Professional Development; Compensation and Incentives; Working Conditions; and Performance Management. Offers a framework and strategies for understanding the issues that make up the teacher quality question Written for educational leaders, superintendents, district administrators, teacher leaders, and principals, as well as policy-makers and other stakeholders Filled with illustrative examples teacher quality The author addresses the most important factor that affects student achievement-the quality of the teacher."--
"This book offers education leaders at all levels innovative strategies based on best practices that are at once proactive, strategic, and coordinated. Resting on the principles of collaboration and common understanding, the authors explore eight necessary components for improving teacher quality."--[book cover].
Teachers and leaders in schools: The condition that support effective teachers and leaders -- Getting the right people on the bus: How school districts manage teacher recruitment, hiring, and placement -- The enduring role of unions: Teacher performance management -- The view from the statehouse: Enabling teachers, building the profession -- Setting the table: the role of institutions of higher education in preparing teachers for success -- Conclusion: Managing educator talent for Gen Y teachers and beyond.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Teacher effectiveness; Teachers -- Rating of; Performance standards; Electronic books